(untitled) (KASBIT Business Journal, 2022)
This study seeks to investigate the effect of shared leadership on project success directly and through the mediation of Team Performance and Degree of Autonomy. The other objective of the current study is to measure the moderating role of communication on the relationship between team performance, job autonomy and project success. Data was collected from 266 team members working on software development projects in Pakistan and was analyzed through SPSS and Smart PLS. The results show that shared leadership directly influences project success in a favorable way (positively) and that this link is mediated by team performance and degree of autonomy. It has been discovered that communication moderates the relationship between team performance, degree of autonomy and project success. The current research work delivers a theoretically useful framework for understanding the success and worth of shared leadership in software development. Specifically, the current results recommend the importance of considering team performance and the appropriate degree of autonomy to increase the success rate in software development projects.